Assessment of adhesive strength of an earth plaster on different substrates through different methods - Faria, Paulina (2020)
The adhesion capacity of an earthen mortar is one of the most important properties for plastering. This paper aims to assess the influence of two different substrates, namely adobe and hollow fired clay bricks, in the adhesive strength of an earth plastering mortar formulated in laboratory, through tensile and shear tests methods. The substrates are prepared differently, with and without prior application of a clay grout. The test samples were produced also differently, by cutting while fresh, cutting after hardening and directly sample moulding. Tests were performed in two different relative humidity environments: 65% and 95%. The results are compared, evaluating the influence of the different parameters, and with results of other plasters. The earth plaster presented a good performance regarding adhesion on both substrates studied, being advantageous the preparation of the support with a clay grout. The cutting procedure of the samples influences the test results being the fresh mortar cut less harmful. The relative humidity increment has a negative effect on the adhesion capacity but even a high percentage does not compromise the stability of the plaster. The shear test proved to be a valid instrument when specific pull-off equipment is not available.